Light verb constructions and their verbal synthetic counterparts : a corpus-based study of present-day Catalan - Georgina Alvarez-Morera (Études romanes de Brno)
This article presents an empirical examination of Catalan light verb constructions (LVCs) based on corpus data from the Corpus textual informatitzat de la llengua catalana (CTILC). The main objective is to analyse the relationship between LVCs and their synthetic verbal counterpart (e.g. donar una resposta 'give an answer' – respondre 'to answer'). The corpus data confirm that the weight of the nominal is an essential variable for the possibilities of interchangeability between the analytic and synthetic expression, that is, LVCs with bare unmodified NVEs are more likely to be interchangeable with a synthetic verb. In terms of the degree of frequency of LVCs, the most frequent lemmas do not exhibit signs of lexicalization, but they are highly interchangeable. These findings reject the view that LVCs coexist with the synthetic verbs because there is no semantic correlation or the LVC has developed a specific lexicalized meaning.